(untitled) (Journal of Advanced Research in Social Sciences, 2022)
Real property right has witnessed tremendous transformations over time due to social, political, and economic conditions that societies have known. Since the French revolution in 1789, property right has been considered as a growth lever, especially for policy makers and social scholars. A new theory states that property right has changed since World War II, both in character and content. The interaction of real property with social and economic conditions has impacted the structure of this right, namely the right to dispose “abusus”. Contrary to its traditional characteristics, real property might, at the present time, be flexible and temporary. In Morocco, property right is sacred. Article 35 of the Moroccan constitution stipulates that the right to property is guaranteed. Unfortunately, in reality the implementation of this constitutional disposition is not always straightforward. It is usually hindered by the existence of multiple legal texts governing real estate property. The main objective of the present paper is to analyze the new real estate property right’s theory in light of the economic changes. We will tackle different aspects of the current fundamental transformation of the law of private property in Morocco, evaluating it from a distributive justice perspective.